RYZYKO ZWIĄZANE Z PODRÓŻAMI MORSKIMI JAKO SZCZEGÓLNEGO RODZAJU WKŁAD NIEPIENIĘŻNY DO SPÓŁKI W PRAWIE RZYMSKIM - Benincasa, Zuzanna (Zeszyty Prawnicze, 2016)
The Risk Connected to Sea Voyages as the Particular Kind of Non-monetary Contribution to Partnership in Roman Law Summary The seaborne commerce in ancient Rome due to the amount of capital required and the risk involved in navigation was often practiced as a common enterprise. The best known form of a common investment in maritime trading was a contract of maritime loan but analogical purposes could be realized through making the consensual contract of societas. This contract could be used to achieve its traditional scope which is collecting a capital necessary for conducting some kind of economic activity and sharing the risk involved in such business. In this kind of partnership each partner made a contribution of capital for financing the partnership’ activity (in the form of money or property) and also each partner was involved in conducting the common business matters. The alternative form was a partnership in which only one partner made a contribution of capital and the other socius contributed his future services that consisted of travelling and trading and as the consequence was exposed to the risk of navigation. Undoubtedly such a partnership operating in the sector of maritime commerce was a very hazardous enterprise because the risk that a ship may perish was very high. Thus the risk of navigation, and more precisely the willingness to undertake such a risk, was treated as a very precious component of a partner’s services and in case of a partnership in which only one partner made such a contribution, his contribution was deemed to be of extreme value and importance and thus justify granting him a special position in a partnership. The problem regarding the willingness to undertake the risk of navigation as a kind of a non-monetary contribution in a partnership was treated by Ulpianus in his commentary ad Sabinum (D. 17,2,29,1). This jurist accepted the possibility of making a partnership in which one partner had a share in the profits but did not bear the loss. Such an agreement was permissible if his services constituted an economical equivalent of the loss. To justify this opinion Ulpianus said that often the services performed by a partner (industria) were of such importance that their value was even higher than the value of the capital contributed by other partners. To illustrate such a situation Ulpianus referred to an example of a partner who alone underwent the danger of navigation (solus navigat solus peregrineretur, pericula subeat solus). The question of an exclusion of one of the partners from bearing the loss constituted one of the issues of the controversy reported in legal sources as magna quaestio. This controversy is deemed to be related with the transformation of a partnership from the community of properties to an instrument of conducting economic activities and gaining profits. On the basis of the sources it is not possible to find out about the role that the latter example played in this controversy. But it’s worth noting that this example constitutes the one and the only example of the situation in which the partner’s non- monetary contribution was deemed to be so precious that justified the settlement on the basis of which this partner was excluded from bearing the loss resulted from the partnership’s business. Thus one can not exclude that this example was also used by Servius and his supporters to popularize more universal idea of excluding the partners that contributed only their services from the loss in the partnership. It is also worth noting also that such a partnership in which one partner made a contribution of capital and the other conducted a partnership business that involved sea-travelling was a contract very close to a maritime loan. For the maritime loan it was essential that the creditor undertook the risk of the perishing of the ship (periculum maris) in which case he was not entitled to claim his money back, but as a reward he could stipulate the interests exceeding the legal rate in case of a successful journey. Thus his situation was analogous to the situation of a partner who contributed his capital in a partnership – both of them were involved in sponsoring a common business but they did not participate in its conducting. If the ship arrived safely both of them participated in the profits: the partner according to his share in partnership, the lender could claim the high interests, but in case of the perishing of the ship both of them lost the money they had invested in a commercial voyage. Respectively a partner who contributed to the partnership with his services and thus undertook the risk of navigation just as a borrower in case of the maritime loan, in case of successful return of the ship had his share in the profit but in case of the perishing of the ship did not bear the loss of an invested capital. Thus the contract of partnership in the moment of the passage from the idea of a partnership based on the ownership to the idea of a partnership as the instrument of conducting economic activities and gaining profits became an alternative to the contract of a maritime loan legal form in which the seaborne commerce could be financed. The risk involved in navigation was thus treated as a value that could constitute a kind of a non-monetary contribution of a partner in partnership’s profits and losses. At the same time the particular character of this contribution was used as an argument in the discussion regarding the general issue of the exclusion of a partner who contributed only with his services from bearing the loss resulted from the partnership’s activities. The acknowledgement of a willingness to undertake the risk of navigation as a possible contribution to the partnership constitutes the proof that the Roman iurisprudentes affirmed that in many cases there wasn’t the capital but services offered by a partner crucial for making profit. These services might consist of special abilities and skills of a partner (ars, peritia), his social position and connections (gratia) or undertaking some hazardous activity for a partnership (industria). The acceptance of these values as crucial for fixing the partners’ shares in a partnership means also the acceptance in the law sector of the elements that were essential in the area of making business. Thanks to that a partnership became a contract that could be attractive for the entrepreneurs who wanted to make profits. Showing the advantages offered by this contract to Roman businessmen, due to the acceptance of such a flexible concept of possible kinds of the contribution, supports the view that the role of this contract in the Roman economy was not as marginal as it was maintained by the authors convinced that the key-figure for conducting common economic activities was a servus communis.